Podcast applications in language learning : a review of recent studies. - Hasan, Md. Masudul; Tan, Bee Hoon (Canadian Center of Science and Education, 2013)
Many dynamic approaches have emerged due to computer technology in facilitating language learning skills. Podcasting is one such novel tool being exploited by teachers to deliver educational content and to encourage learning outside the classroom. Research on podcasting pedagogy suggests that podcasting greatly helps learners develop various skills of English language. The study reviewed twenty journal articles to determine the effects of podcast on ESL students’ language skills and attitude levels. It was found that podcasts greatly support learning not just in speaking and listening but also in other language skills and areas such as grammar, pronunciation and vocabulary.